Variable range hopping conduction and microstructure properties of semiconducting Co-doped TiO2 - Okutan, M; Bakan, HI; Korkmaz, K; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2005)
The surface morphology, phases existing in the microstructure and conductivity behavior of Co-doped TiO2 have been investigated by atomic force microscopy (AFM), scanning electron microscopy (SEM), electrical conductivity measurements and X-ray diffraction technique. The semiconducting phase is found to obey Mott's variable range hopping mechanism of the conduction. The conduction mechanism of the ceramic shows a crossover from the, exp[-(T-0/T)(1/4)] law to a simply activated law, exp(-DeltaE/kT). This behavior is attributed to temperature-induced transition from 3D to thermally activated behavior. The hopping conduction parameters such as the characteristic temperature (T-0), localization length (alpha), hopping distance (R), activation energy (DeltaE) and density of states at Fermi level (N(E-F) have been calculated. Surface morphology shows that the ceramic has a regular surface. The SEM study indicates that there are grains which have a certain type in the microstructure. Rutile phases with different plane in microstructure were found. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: semiconductor; TiO2; doping; conduction mechanism